Reliability of follicle-stimulating hormone measurements in serum - Kaaks Rudolf; Rinaldi Sabina; Lukanova Annekatrin; Zeleniuch-Jacquotte Anne; Arslan Alan A; Toniolo Paolo (BMC, 2003)
Abstract Background Follicle-stimulating hormone (FSH), a member of gonadotropin family, is critical for follicular maturation and ovarian steroidogenesis. Serum FSH levels are known to fluctuate during different phases of menstrual cycle in premenopausal women, and increase considerably after the menopause as a result of ovarian function cessation. There is little existing evidence to guide researchers in estimating the reliability of serum FSH measurements. The objective of this study was to assess the reliability of FSH measurement using stored sera from an ongoing prospective cohort - the NYU Women's Health Study. Methods Sixty healthy women (16 premenopausal, 44 postmenopausal), who donated at least two blood samples at approximately 1-year intervals were studied. An immunoradiometric assay using a sandwich monoclonal antibodies technique was used to measure FSH levels in serum. Results The reliability of a single log-transformed FSH measurement, as determined by the intraclass correlation coefficient, was 0.70 for postmenopausal women (95% confidence interval (CI), 0.55-0.82) and 0.09 for premenopausal women (95% CI, 0-0.54). Conclusions These results suggest that a single measurement is sufficient to characterize the serum FSH level in postmenopausal women and could be a useful tool in epidemiological research. For premenopausal women, however, the reliability coefficient was low, suggesting that a single determination is insufficient to reliably estimate a woman's true average serum FSH level and repeated measurements are desirable.